2017
DOI: 10.1186/s40663-016-0088-1
|View full text |Cite
|
Sign up to set email alerts
|

Response of understory vegetation over 10 years after thinning in an old-growth cedar and cypress plantation overgrazed by sika deer in eastern Japan

Abstract: Response of understory vegetation over 10 years after thinning in an old-growth cedar and cypress plantation overgrazed by sika deer in eastern Japan Atsushi Tamura * and Masanobu Yamane Abstract Background: Forest management strategies such as thinning have long been used to enhance ecosystem functions, especially in plantations. Thinning in plantations with high deer density, however, may not yield a desired increase in understory vegetation because deer graze on germinating plants after thinning. Here, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…It has been found that the implementation of thinning practices improved the growth spaces and light transmittance in stands by reducing the canopy densities, and ultimately enhanced the growth of both the reserved trees and understory plants (Ares, Neill & Puettmann, 2010;Cheng, Yu & Wu, 2013;Verschuyl et al, 2011). Previous studies have extensively surveyed the impacts of thinning on the diversity and biomass of understory vegetation (Cheng et al, 2014;Dang et al, 2018;Tamura & Yamane, 2017;Wen, Cheng & Liu, 2008), as well as the effects on tree growth rates (Gong, Niu & Mu, 2015;Wu et al, 2015), physical and chemical characteristics of the soil (Wang et al, 2013;Zhou et al, 2016), and even the soil microbial biomass (Kim et al, 2018;Thibodeau et al, 2000), nutrient transformations (Boerner et al, 2008), and soil respiration characteristics (Akburak & Makineci, 2015;Tang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the implementation of thinning practices improved the growth spaces and light transmittance in stands by reducing the canopy densities, and ultimately enhanced the growth of both the reserved trees and understory plants (Ares, Neill & Puettmann, 2010;Cheng, Yu & Wu, 2013;Verschuyl et al, 2011). Previous studies have extensively surveyed the impacts of thinning on the diversity and biomass of understory vegetation (Cheng et al, 2014;Dang et al, 2018;Tamura & Yamane, 2017;Wen, Cheng & Liu, 2008), as well as the effects on tree growth rates (Gong, Niu & Mu, 2015;Wu et al, 2015), physical and chemical characteristics of the soil (Wang et al, 2013;Zhou et al, 2016), and even the soil microbial biomass (Kim et al, 2018;Thibodeau et al, 2000), nutrient transformations (Boerner et al, 2008), and soil respiration characteristics (Akburak & Makineci, 2015;Tang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Frontiers in Microbiology frontiersin.org were notably higher than those in the control. The main reason is that thinning results in more or larger canopy gaps and improves understory light conditions, which increases plant diversity (Tamura and Yamane, 2017). However, the effect of thinning on the richness of the herb layer was not as obvious as those in previous reports (Son et al, 2004;Muscolo et al, 2021), and the species richness was greater in the shrub layer than in the herb layer.…”
Section: A B Figurementioning
confidence: 61%
“…Such instances are attributed to grazing by deer (Tamura & Yamane, 2017), and so the effectiveness of thinning in Japan and other northern temperate nations that similarly are experiencing high deer densities (Côté, Rooney, Tremblay, Dussault, Waller, 2004), will likely depend on local deer densities and grazing management. Such instances are attributed to grazing by deer (Tamura & Yamane, 2017), and so the effectiveness of thinning in Japan and other northern temperate nations that similarly are experiencing high deer densities (Côté, Rooney, Tremblay, Dussault, Waller, 2004), will likely depend on local deer densities and grazing management.…”
Section: Effects Of Plantation Management On Biodiversitymentioning
confidence: 99%
“…Our explanatory power was low for models explaining understory abundance with thinning intensity and stand age, and previous research has shown that thinning resulted in almost no increase in understory vegetation. Such instances are attributed to grazing by deer (Tamura & Yamane, 2017), and so the effectiveness of thinning in Japan and other northern temperate nations that similarly are experiencing high deer densities (Côté, Rooney, Tremblay, Dussault, Waller, 2004), will likely depend on local deer densities and grazing management.…”
Section: Effects Of Plantation Management On Biodiversitymentioning
confidence: 99%